2011
DOI: 10.1038/nrrheum.2011.168
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular safety of biologic therapies for the treatment of RA

Abstract: Cardiovascular disease represents a major source of extra-articular comorbidity in patients with rheumatoid arthritis (RA). A combination of traditional cardiovascular risk factors and RA-related factors accounts for the excess risk in RA. Among RA-related factors, chronic systemic inflammation has been implicated in the pathogenesis and progression of atherosclerosis. A growing body of evidence--mainly derived from observational databases and registries--suggests that specific RA therapies, including methotre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 100 publications
1
33
1
Order By: Relevance
“…But the association between anti-TNFs and fewer cardiovascular events is consistent across registers, time of publication, ages and socioeconomic groups [13,47,60]. Regarding solid cancers, we did not found excess risk under anti-TNF.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…But the association between anti-TNFs and fewer cardiovascular events is consistent across registers, time of publication, ages and socioeconomic groups [13,47,60]. Regarding solid cancers, we did not found excess risk under anti-TNF.…”
Section: Discussioncontrasting
confidence: 51%
“…According to the Swedish Biologics Register (ARTIS), no major differences in cancer stage at diagnosis or in post-cancer survival were observed as compared to biologics-naive RA patients with cancer [34]. Only 2 studies from RABBIT and CORRONA registers reported data on cancer under non anti-TNFs treatment: no increased risk of cancer was detected with anakinra comparing to cDMARD (adjusted hazard ratio = 1.4 [0.6-3.5]) [13], with abatacept (HR = 1.55 [0.40-5.97]) and rituximab (HR = 0.42 [0.07-2.60]) comparing to methotrexate [35].…”
Section: Solid Cancersmentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, acute phase reactants (APRs), typically elevated in RA, have been shown to be associated with subclinical atherosclerosis, indicated by increased carotid artery intima–media thickness (cIMT) [56] and CV morbidity and mortality in patients with RA [57]. In the general population, CRP level is an independent predictor of CV risk, particularly MI [58], while in both RA patients and healthy subjects, CRP is associated with the number of atherosclerotic plaques and cIMT [49, 59].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-TNF-α therapy has been reported to decrease cardiovascular risk in RA, with multiple reasons being attributed to this reduction: decreased systemic inflammation, corticoid-sparing effects, and increased high density lipoprotein (HDL) levels [5,6] but the exact underlying mechanism(s) have been widely debated [7].…”
Section: Introductionmentioning
confidence: 99%